2015
DOI: 10.1101/030288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of 375,000 individuals identifies 38 susceptibility loci for migraine

Abstract: Migraine is a debilitating neurological disorder affecting around 1 in 7 people worldwide, but its molecular mechanisms remain poorly understood. Some debate exists over whether migraine is a disease of vascular dysfunction, or a result of neuronal dysfunction with secondary vascular changes. Genome-wide association (GWA) studies have thus far identified 13 independent loci associated with migraine. To identify new susceptibility loci, we performed the largest genetic study of migraine to date, comprising 59,6… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 80 publications
0
7
0
4
Order By: Relevance
“…3 Taking into account that ACE is a transmembrane metalloproteinase, identification of genes linked to metal ion homeostasis, in addition to the neuronal and vascular genes in large genome-wide association studies in migraine is imperative. 69 As a complex "neuro-vasculo-inflammatory" disease, vasodilatation in cephalic vasculature and inflammatory process following the sensitization/activation of the trigeminovascular system and CGRP along with other neuropeptide releases are the central mechanisms of migraine attacks. 70,71 Endothelial cells play a crucial role in the control of vascular signaling process, maintenance of vascular barrier, blood coagulation, and also mediate immune signaling pathways.…”
Section: Fig 3-the Diagram Summarizing the Hypothetical Mechanisms Of The Inflammatory Activation In The Microvasculature In Covid-19 Vasmentioning
confidence: 99%
“…3 Taking into account that ACE is a transmembrane metalloproteinase, identification of genes linked to metal ion homeostasis, in addition to the neuronal and vascular genes in large genome-wide association studies in migraine is imperative. 69 As a complex "neuro-vasculo-inflammatory" disease, vasodilatation in cephalic vasculature and inflammatory process following the sensitization/activation of the trigeminovascular system and CGRP along with other neuropeptide releases are the central mechanisms of migraine attacks. 70,71 Endothelial cells play a crucial role in the control of vascular signaling process, maintenance of vascular barrier, blood coagulation, and also mediate immune signaling pathways.…”
Section: Fig 3-the Diagram Summarizing the Hypothetical Mechanisms Of The Inflammatory Activation In The Microvasculature In Covid-19 Vasmentioning
confidence: 99%
“…To analyse the genetic overlap between CPSP and chronic peripheral pain syndromes, recent GWAS studies were used to form PRS scores in order to differentiate between patients who developed CPSP and those who did not. Using PubMed, we identified 6 GWAS reports on chronic pain syndromes (sciatic pain, migraine, chronic widespread pain, osteoarthritis, rheumatoid arthritis, and cluster headache) meeting the inclusion criteria [11,12,[26][27][28][29][30]: The headache-related disorders (migraine and cluster headache) were selected as negative control due to a different pathophysiology [31,32]. A total of 7208 SNPs were reported as summary statistics in migraine, of which 214 were present after pruning in the discovery cohort and 207 after pruning in the replication cohort [11].…”
Section: Cohort Selection For Polygenic Risk Score Calculationmentioning
confidence: 99%
“…targeted studies) defines a potential role for genetic risk factors in CPSP, the limited CPSP sample size in comparison with studies of other chronic pain syndromes has thus far not provided clear candidate genes for CPSP [9][10][11][12]. While increasing sample size for GWAS analyses holds the potential for unambiguous identification of genetic risk factors, genetic mechanisms underlying CPSP may be probed indirectly by determination of common genetic factors with other pain syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies provided evidence that common types of migraine are genetically complex: multiple genetic variants with small effect sizes act together with environmental factors to confer migraine susceptibility (Gormley and others 2018). Interestingly, those studies have identified other variants in genes encoding K 2P channels, namely KCNK5 (TASK2, Twik-related acid sensing K + channel) (Gormley and others 2016) and KCNK4 (TRAAK, Twik-related arachidonic acid stimulated K + channel). It is also of note that migraine has a genetic overlap with psychiatric disorders, especially depression, in which K 2P channels have been also shown to play a role (Djillani and others 2019;Heurteaux and others, 2006).…”
Section: Genetic Aspectsmentioning
confidence: 99%